2021
DOI: 10.2174/1567205018666210324130502
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Brain Imaging Biomarker for AD and aMCI: ALFF in Slow-5 Frequency Band

Abstract: Background: As a potential brain imaging biomarker, amplitude of low frequency fluc-tuation (ALFF) has been used as a feature to distinguish patients with Alzheimer’s disease (AD) and amnestic mild cognitive impairment (aMCI) from normal controls (NC). However, it remains unclear whether the frequency-dependent pattern of ALFF alterations can effectively distinguish the different phases of the disease. Methods: In the present study, 52 AD and 50 aMCI patients were enrolled together with 43 NC in total. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…To evaluate the classification ability of the SVM model, the accuracy, sensitivity, specificity and precision were calculated, and the receiver operating characteristic (ROC) curve of the classifier is shown in Figure 2 . The curve was drawn using Receiver Operating Characteristic Assistant software ( Wang et al, 2021 ). The performance of the classifier achieved an accuracy of 80.90%, sensitivity of 77.08%, specificity of 85.37%, precision of 86.05%, and area under curve (AUC) of 0.8501 for TIA vs. HCs.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the classification ability of the SVM model, the accuracy, sensitivity, specificity and precision were calculated, and the receiver operating characteristic (ROC) curve of the classifier is shown in Figure 2 . The curve was drawn using Receiver Operating Characteristic Assistant software ( Wang et al, 2021 ). The performance of the classifier achieved an accuracy of 80.90%, sensitivity of 77.08%, specificity of 85.37%, precision of 86.05%, and area under curve (AUC) of 0.8501 for TIA vs. HCs.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, these ALFF changes were found to exhibit a frequency-dependent pattern ( Han et al, 2011 ; Liu et al, 2014 ). In our previous study, we observed the difference in ALFF in the slow-5 frequency band between groups, mainly corresponding to the bilateral hippocampus as well as regions within the default mode network, with the highest accuracy in discriminating the three groups ( Wang et al, 2021 ). Our findings indicated that ALFF in the slow-5 frequency band might serve as a promising functional indicator to aid the diagnosis of AD and aMCI ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 88%
“…In our previous study, we observed the difference in ALFF in the slow-5 frequency band between groups, mainly corresponding to the bilateral hippocampus as well as regions within the default mode network, with the highest accuracy in discriminating the three groups ( Wang et al, 2021 ). Our findings indicated that ALFF in the slow-5 frequency band might serve as a promising functional indicator to aid the diagnosis of AD and aMCI ( Wang et al, 2021 ). Recently, ALFF combined with structural features has been investigated for the diagnosis of AD and aMCI ( Khatri and Kwon, 2022 ; Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations